The economic Impacts of Increasing Direct and Indirect Taxes In Syria: Applied Study Using The Computable General Equilibrium Model (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2018)
This study aims to identifying the best options and alternatives to increase the government's financial resources required to finance the various items on the government expenditure list throw  increase tax revenues and study the economic impacts of this increase. Given the special importance of this topic as well as its economic and social sensitivity, the study choose to employ one of the most important tools used in this regard i.e. the computable general equilibrium models (CGE). For that, a static computable general equilibrium model is built according to the Syrian case, this model is based on the social accounting matrix that was built for the purpose of analyzing tax policy in Syria, mathematical and statistical tools were used to estimate the parameters of the model. At the last, software GAMS  has been used to solve the model. After finalizing the model and testing its prediction power, the effects of the independent  variables( rate of direct and indirect taxes) on the dependent variables(GDP,GOVCON,INVEST,EXP,EXP, IMP) were studied by run two simulation  to increase tax rates for both direct and indirect taxes. Then, the study tested the impacts of employing each scenario by increasing the tax rate by 10% separately for each type of tax. The results showed that there is a possibility of increasing direct taxes without imposing negative impact on the other economic variables in the model except marginal propensity to save, but there were several negative results on all variables except government consumption and government income associated with the use of indirect taxes. الآثار الاقتصادية لزيادة الضرائب المباشرة وغير المباشرة في سورية: دراسة تطبيقية باستخدام تقنية نموذج التوازن العام المحوسب هدف البحث هو تحديد أفضل الخيارات والبدائل الممكنة لزيادة الموارد المالية للحكومة اللازمة لتمويل بنود إنفاقها المختلفة من خلال زيادة الإيرادات الضريبية ودراسة الآثار الاقتصادية لهذه الزيادة. ولأهمية هذا الموضوع وحساسيته الاقتصادية والاجتماعية اختار البحث واحدة من أهم الأدوات المستخدمة في هذا المجال وهي نماذج التوازن العام المحوسبة (CGE)، حيث تم بناء نموذج توازن عام سكوني خاص بسورية، انطلاقاً من إعداد مصفوفة محاسبة اجتماعية خاصة بهذا النموذج، ومن ثم انتقلت الدراسة إلى تقدير معالم النموذج بالاعتماد على الأساليب الرياضية والإحصائية في ذلك، بعد ذلك تم إدخال البيانات وحل النموذج باستخدام برمجية GAMS. بعد حل النموذج واختبار قدرته على التنبؤ، تمت دراسة أثر متغيرات البحث المستقلة (معدل الضرائب المباشر، معدل الضرائب غير المباشرة) على المتغيرات التابعة (الناتج المحلي الإجمالي، الاستهلاك العام، الاستهلاك الخاص، الدخل الحكومي، الإنفاق الحكومي، الميل الحدي للادخار، مجمل الاستثمار، الصادرات، الواردات) من خلال تشغيل محاكاة لزيادة كل من معدلي الضرائب المباشرة وغير المباشرة بنسبة 10%، واختبار الآثار المترتبة لكل سيناريو على حدة. بيّنت النتائج إمكانية زيادة الضرائب المباشرة دون أن يكون لها منعكسات سلبية على متغيرات الدراسة، باستثناء الميل الحدي للادخار, وكان هناك آثار سلبية لزيادة معدل الضرائب غير المباشرة على جميع المتغيرات باستثناء الاستهلاك العام والدخل الحكومي.